A text mining analysis of preservice teachers’ reflective discourses in online teaching: basis for a policy brief - Tolentino, Julius Ceazar G.; Miranda, John Paul P. (Intelektual Pustaka Media Utama, 2026)
This study examined the reflections of 142 preservice teachers who taught online during the COVID-19 pandemic. This study identified common themes, emotions, and patterns in their experiences using sentiment analysis and hierarchical clustering. The most frequently used words, such as “learn,” “experience,” and “time,” highlight themes of learning and action. Sentiment analysis shows that most of their reflections are positive, using words like “well,” “good,” and “great.” Hierarchical clustering revealed three main themes in their reflections: i) professional growth and development; ii) passion for teaching and connection; and iii) adaptability and resilience. These themes show the complex nature of their experiences. While focusing on personal and professional growth, a strong commitment to teaching, and adaptability in challenging situations was evidenced. The findings of this study will help create a policy brief addressing these themes. Recommendations include strategies for professional growth in online teaching, encouraging a love for teaching through online platforms, and improving teacher training programs to build adaptability and resilience. Policymakers and educators can use these insights to develop effective policies and practices that support preservice teachers in online teaching even during health crises or similar disruptions.